Anatomical considerations, testicular, and scrotal anatomy of nonobstructive azoospermia patients - Hao-Cheng Lin; Yan Chen; Yang-Yi Fang; Kai Hong (Asian Journal of Andrology)
Infertility, defined as the inability to conceive after 1 year of regular unprotected intercourse, impacts 10%–20% of couples globally. Both male and female factors contribute equally to this condition. Azoospermia, particularly nonobstructive azoospermia (NOA), which affects 10%–15% of infertile men, represents a significant challenge in male infertility. The advent of assisted reproductive technology (ART), specifically microdissection testicular sperm extraction (micro-TESE) followed by intracytoplasmic sperm injection (ICSI), offers a possibility for men with NOA to father biological children. Recent studies have focused on the predictors of sperm retrieval in NOA patients, such as age, testicular volume, and follicle-stimulating hormone (FSH) level. This review aims to explore the limited data on the anatomical characteristics of NOA patients and provide surgical considerations for micro-TESE, thereby enhancing understanding and improving outcomes for this challenging condition.